Electrochemotherapy using thin-needle electrode improves recovery in feline nasal planum squamous cell carcinoma - a translational model - Tellado, Matías Nicolás (2022)
Aim: Cutaneous squamous cell carcinoma (cSCC) is a common disease in patients exposed to UV-light and human papillomavirus. Electrochemotherapy, a well-established treatment modality with minimum side effects in human and veterinary medicine, circumvents chemoresistance to bleomycin by the use of electric fields. However, patients are sensitive to the trauma produced by the insertion of the needles that lengthen recovery times, particularly cats with nasal planum cSCC. To address this matter, we developed thin-needles electrodes. Methods: Thin-needles electrodes developed using computer simulations and plant tissue models were compared to standard electrodes. A prospective non-randomized study recruiting 52 feline patients with nasal planum cSCC was performed. Local response, anorexia, and overall survival were evaluated. Results: Computer simulations and plant model experiments showed satisfactory results with both electrodes. The patients treated with the thin-needle electrode obtained similar local response rates compared to the standard group, OR 97.3% vs. 80%, respectively (P < 0.067). Most patients in the thin-needle group resumed eating in less than 48 h, as the anorexia was significantly lower (P < 0.0001). Using the standard electrode, most patients took 3 to 5 days to resume normal feeding. The electric current circulating in the standard electrode was 44% higher, contributing to a longer duration of anorexia due to tissue damage. The overall survival in both groups was similar. Conclusion: Electrochemotherapy using thin-needle electrodes provides equivalent local response rates and overall survival compared with standard electrodes but significantly reduced return to appetite after the treatment. These results may be useful in the development of new electrodes for human patients.